Reversed Burden of Proof in the Procedural Law of Corruption Cases: A Normative Study of Justice and Legal Certainty in Positive and Islamic Law - Ahmad Hadi Prayitno; Achmad Arifulloh; Toni Triyanto; Setiawan Widiyoko; Moh Aris Siswanto (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2025)
This study examines the reversed burden of proof in the procedural law of corruption cases in Indonesia, focusing on its compatibility with the principles of justice and legal certainty from both positive and Islamic legal perspectives. The method used is normative legal research with a comparative approach between national positive law regulations and Islamic legal principles. The findings show that the reverse burden of proof in Indonesia, as regulated in positive law, is an important tool to combat corruption by shifting the burden of proof to the defendant to prove that their wealth is not derived from corruption. However, the procedural application of this mechanism within the criminal justice system still faces several challenges, including inconsistencies in its enforcement and the limited scope of existing statutory provisions, thereby failing to fully ensure legal certainty. The study of Islamic law emphasizes the importance of the principles of justice (‘adl) and legal certainty (yaqin) in law enforcement, highlighting the need to align the reverse burden of proof mechanism with these values to avoid injustice toward the defendant. Therefore, this study recommends integrating Islamic legal principles with the positive law framework and adopting the “beyond a reasonable doubt” principle as a complementary approach to strengthen fair and legally certain corruption eradication efforts. The academic contribution of this research lies in advancing the discourse of fiqh siyasah and Islamic criminal law by situating the reversed burden of proof within a procedural structure grounded in sharia-based justice and legal certainty, while offering normative recommendations for reforming Indonesia’s evidentiary system in criminal procedure to make it more responsive to Islamic values and universal principles of justice